Structural detection of goaf based on three-dimensional ERT technology - Nan Jia (Systems and Soft Computing)
Goaf, as an underground space formed after mining, the accurate detection of its structure is crucial to mine safety and the stability of underground engineering. Although traditional detection methods, such as drilling and seismic methods, can provide certain information, they have limitations in terms of accuracy and economy. Therefore, this study used three-dimensional electrical resistivity tomography technology to more accurately detect the structure of the goaf due to its high resolution and non-invasive characteristics. At start, the development mechanism of the goaf was analyzed, and then the resistivity three-dimensional tomography technology was used to detect the goaf in the selected area through numerical simulation. The results show that when the surface deformation degree reaches 1.38%, the corresponding error of electrical resistivity tomography technology detection is 1.74%. When the surface deformation degree is 0.58% and 1.36% respectively, the corresponding errors of Multi-physics field monitoring method and the downhole transient electromagnetic method are 1.97% and 1.84% respectively. In the comparison of false negative rate, when the detection area reaches 76.8% of the regional detection area, electrical resistivity tomography technology has the lowest false negative rate, with a value of 2.412%. The accuracy of different methods was tested in the Jinggong and Open-pit areas. When the detection time was 0.51 s and 0.23 s respectively, the ERT method had the highest detection rate, with values approaching 98.57% and 100.00% respectively. During the whole process, the accuracy of the DTEM method was 87.85% and 99.99% respectively, which was much lower than that of the ERT method. An analysis of the low-resistivity anomaly areas in the selected study area found that the distribution of the observed areas showed uneven continuity, and its resistivity was low and significantly different from the surrounding rock formations. The above results illustrate that the main advantage of 3D ERT technology is its ability to provide real-time, high-density resistivity data, thereby enabling precise capture of subtle structural changes in the goaf. Compared with traditional methods, 3D ERT not only reduces environmental interference, but also significantly improves the efficiency of data collection and the accuracy of analysis, providing a new technical means for mine safety management and underground engineering.